Performing inter-professional expertise in rural advisory networks. (July 2016) - Phillipson, Jeremy; Proctor, Amy; Emery, Steven B.; Lowe, Philip
Highlights: Rural advisers face demands to work together to help farmers and land managers deliver multiple objectives. Advisers must carefully manage and negotiate interactions with other professionals. Specific skills and strategies make-up their inter-professional expertise. Inter-professional expertise is realised through the interaction of experts in the field. Inter-professional strategies lead to new hierarchies of expertise. Abstract: In this paper we draw on in-depth research to explore inter-professional working in rural land and livestock management and introduce the novel concept of inter-professional expertise . An increasingly intricate regulatory framework, the diversification of the economic base of rural areas away from primary commodity production and a growing emphasis on environmental protection and ecosystem services mean that the management of land and livestock are becoming more complex in their objectives, more demanding of specialised technical knowledge and skills and more rule-bound in their procedures and processes. To assist them in meeting these challenges, farmers and other land managers turn to a growing array of rural professional advisers. Increasingly the achievement of private and public objectives for rural businesses depends upon the integration of a variety of specialised expert inputs. So, alongside pressures to differentiate the specialised knowledge they have to offer, rural professionals face demands to work together to help clients solve complex problems and deliver multiple objectives. It follows that rural land and livestock management present a rich context in which to explore the dynamic relationship between different types of professional experts. As a departure from the strong tradition of farmer-centred research examining extended knowledge networks in rural settings, we therefore explore the working relations between advisers themselves. Using concepts of relational agency and socio-material approaches we identify the skills and strategies involved in this inter-professional communication and working, with relevance to expert-expert interactions and the negotiation of contemporary professional expertise in fields far beyond the provision of rural services. We find that it is in the ways that experts perform, act and interact in the field that professional expertise and, by extension, inter-professional expertise – is realised and practised. Thus as working practices are increasingly shared, credentialism is pursued less by achieving the monopolies of old and more by striving for new monopolies of inter-professional practice.